Systematic review and meta-analysis to assess the safety of Buproprion and Varenicline in pregnancy - Turner, Emily; Jones, Matthew; Vaz, Luis R.; Coleman, Tim (Oxford University Press, 2018)
Introduction: Smoking in pregnancy is a substantial public health issue, but, apart from nicotine replacement therapy (NRT), pharmacological therapies are not generally used to promote cessation. Bupropion and varenicline are effective cessation methods in non-pregnant smokers and this systematic review investigates their safety in pregnancy.